(untitled) (Revista de Ensino em Artes, Moda e Design, 2026)
This article presents an interdisciplinary pedagogical experience which integrates architecture, scenography and copyright fashion within Interior Architecture for Scenography course at a private university. The research, anchored in the concepts of ethnography and auto ethnography, is qualitative, exploratory, and descriptive, is based on two students’ experience report who reflect on pedagogical practice and the theoretical foundations which guided The Dynamic Modules methodology, grounded on Project-Based Learning, three challenges were structured throughout the semester: camera scenography, stage scenography, and experiential scenography. All of them encompassed case studies, technical visits, lectures, conceptual and project development, and presentations using different techniques, fostering communication and expressive skills. In the camera scenography module, the students report their experience developing scenic spaces for a talk show on Brazilian copyright fashion, conceived by them, valuing local narratives, cultural identity, and the aesthetics of “do-it-yourself”. The process involved defining the target audience, planning the script, creating sets, and presenting them through models, a semantic panel, and a video. The study highlighted the convergence among architecture, fashion, and scenography as a field of aesthetics and conceptual experimentation, showing that the methodology adopted promotes autonomy, critical thinking, and interdisciplinary guided towards transdisciplinary, preparing students for real challenges in professional practice through a sensitive and culturally integrated approach.